SPECIFIC SERUM IMMUNOGLOBULIN G TO CHLAMYDIA PNEUMONIAE IN HEALTHY CHILDREN AND ADULTS (SOUTH-EAST OF IRAN) - Nemati, Maryam; Mirzaee, Vahid; Shaabani, Ziba; Zarrin, Moein; Mirabdolahi, Sayed Ali; Bagheri-Jamebozorgi, Masoomeh; Rezayati, Mohammad-Taghi; Jafarzadeh, Abdollah (Journal of Ayub Medical College Abbottabad, 2015)
Background: Chlamydia pneumoniae (C. pneumonia) is an obligate intracellular bacterium and recognized as a risk factor for several diseases such as asthma, atherosclerosis and arthritis. The aim of this study was to determine the sero-prevalence of C. pneumonia in healthy subjects in different age groups. Methods: The serum levels of anti C. pneumonia IgG were measured by using of ELISA. Results: Totally, 630 subjects (164 children and 466 adults) were included into study. The sero-prevalence and the mean titer of anti C. pneumonia antibody were 11.3% and 14.48±2.18 RU/mL; at age ‰¤10 years, 15% and 17.47±2.40 RU/mL at age 11-20 years, 21% and 25.15±4.56 RU/mL at age 21-30 years group, 40% and 53.77±6.40 RU/mL at age 31-40 years, 94% and 146.41±8.95 RU/mL at age 41-50 years, 98% and 153.59±10.38 RU/mL at age 51-60 years, 96% and 138.80±12.78 RU/mL at age 61-70 years, respectively. The differences of the sero-prevalence and the mean titer of anti C. pneumonia antibody between age groups were significant (p<0.0001). The sero-prevalence and the mean titer of anti C. pneumonia antibody were 11.6% and 14.33 ± 1.49 RU/mL in children and 65.5% and 97.40±4.46 RU/mL in adults. The sero-prevalence and the mean titer of anti C. pneumonia antibody were significantly higher in adults in comparison with those in children (p<0.0001). Conclusion: These findings showed that the sero-prevalence and titer of anti C. pneumonia IgG were increased with advanced ages and were higher in adults as compared to children. Keywords: Chlamydia pneumonia; IgG; Sero-prevalence; Age; Adults; Children; Iran